DNA Vaccines: Developing New Strategies against Cancer. (28th March 2010) - Fioretti, Daniela; Iurescia, Sandra; Fazio, Vito Michele; Rinaldi, Monica
Abstract : Due to their rapid and widespread development, DNA vaccines have entered into a variety of human clinical trials for vaccines against various diseases including cancer. Evidence that DNA vaccines are well tolerated and have an excellent safety profile proved to be of advantage as many clinical trials combines the first phase with the second, saving both time and money. It is clear from the results obtained in clinical trials that such DNA vaccines require much improvement in antigen expression and delivery methods to make them sufficiently effective in the clinic. Similarly, it is clear that additional strategies are required to activate effective immunity against poorly immunogenic tumor antigens. Engineering vaccine design for manipulating antigen presentation and processing pathways is one of the most important aspects that can be easily handled in the DNA vaccine technology. Several approaches have been investigated including DNA vaccine engineering, co-delivery of immunomodulatory molecules, safe routes of administration, prime-boost regimen and strategies to break the immunosuppressive networks mechanisms adopted by malignant cells to prevent immune cell function. Combined or single strategies to enhance the efficacy and immunogenicity of DNA vaccines are applied in completed and ongoing clinical trials, where the safety and tolerability of the DNA platform are substantiated. In this review on DNA vaccines, salient aspects on this topic going from basic research to the clinic are evaluated. Some representative DNA cancer vaccine studies are also discussed.